URBAN MIGRATION ATTRACTION AS INDICATOR OF TRANSFORMATION OF THE RUSSIAN POST-SOVIET URBAN SPACE - Tatyana Grigorievna Nefedova (Наука. Инновации. Технологии, 2022)
In this article we analyze the migration balance of cities of different sizes in different macro-regions of Russia from 1970 and the most detail for the period 1991-2011, reviews progress of urbanization in the country and its transformation of urban space in the post-Soviet period.